2022
DOI: 10.1155/2022/2162981
|View full text |Cite|
|
Sign up to set email alerts
|

Data Sharing Method of College Dance Teaching Resource Database Based on PSO Algorithm

Abstract: Aiming at the problems of long sharing time, low accuracy, recall, and F1 value in the traditional data sharing method of college dance teaching resource database, a data sharing method of college dance teaching resource database based on PSO algorithm is proposed. Multiple regression KNN method is used to eliminate the data noise of college dance teaching resource database, so as to obtain the missing value and complete the filling of incomplete data of college dance teaching resource database. Taking the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…With rapid development of information technology and widespread application of the Internet, online sharing of digital teaching resources has become an important trend in the field of education today [1][2][3][4][5][6]. This sharing mechanism converts traditional paper teaching materials and multimedia teaching resources into digital formats, which provides teachers and students with a convenient and efficient way to access and utilize educational resources [7][8][9][10][11], offers interactive functions, such as real-time communication, online discussion, and questions and answers, and supports knowledge sharing and collaborative learning between teachers and students [12][13][14][15][16][17], thus helping improve teaching quality, and promoting knowledge dissemination and educational equality [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…With rapid development of information technology and widespread application of the Internet, online sharing of digital teaching resources has become an important trend in the field of education today [1][2][3][4][5][6]. This sharing mechanism converts traditional paper teaching materials and multimedia teaching resources into digital formats, which provides teachers and students with a convenient and efficient way to access and utilize educational resources [7][8][9][10][11], offers interactive functions, such as real-time communication, online discussion, and questions and answers, and supports knowledge sharing and collaborative learning between teachers and students [12][13][14][15][16][17], thus helping improve teaching quality, and promoting knowledge dissemination and educational equality [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%